PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) PADA PT. Dok dan Perkapalan Surabaya (Persero) (Studi Pada Satuan Pengawasan Intern) - Veni Handra Yanni (Publika, 2013)
Applied of Good Corporate Governance (GCG) refers to the change of globalization era concerning to economics happens in many countries also impact in Indonesia. It is a method to improve the unfavorable business management to establish a healthy corporation. Related to the statement above, PT. Dok dan Perkapalan Surabaya (Persero) is demanded to increase business job by Good Corporate Governance (GCG) applied. The problems of the study are : (1) How is the applied of Good Corporate Governance (GCG) in PT. Dok dan Perkapalan Surabaya (Persero)?( 2) what is the benefit of the applied of Good Corporate Governance (GCG) in PT. Dok dan Perkapalan Surabaya (Persero)?Applied of Good Corporate Governance (GCG) is the structure by stakeholder, commissioner, and manager to arrange business objectives and tools to get objectives itself and control the job.This research used descriptive qualitative method focus on (1) transparency (2) self-employed (3) accountability (4) responsibility (5) fittingness. This research held in PT. Dok dan Perkapalan Surabaya (Persero) located on Tanjung Perak Barat Street 433-435 Surabaya, exactly in Internal Control Unit division. Subject in this research was the employees in Internal Control Unit, Human Resources, and General Secretariat di PT. Dok dan Perkapalan Surabaya (Persero). Data collection method used interview, observation, and documentation. Whereas data analysis method used data collection, data reduction, data presentation, and conclusion drawing. Result shown that the application of Good Corporate Governance (GCG) in PT. Dok dan Perkapalan Surabaya (Persero) was success enough although it has not maximal yet. It can be seen by (1) observed from five aspects of GCG applied have each regulation so the reference is more clear because PT. Dok dan Perkapalan Surabaya (Persero) have regulation related to GCG, like manual of Corporate Governance, and Code of Conduct. However there was still obstacle in minimum of sosialisation doing by business so it should insert and sosialize the mean of G DPS G in each opportunity. (2) observed from benefit of GCG applied can be seen from the increasing of conviction and belief of shareholder and stakeholder to PT. Dok dan Perkapalan Surabaya (Persero) so impact to image owned by business. The researcher suggest that it should have intern work between business and Internal Control Unit in perform of GCG applied, increase human resources of PT. Dok dan Perkapalan Surabaya (Persero), add supporting facilities making easy Internal Control Unit so it can work professionally.Keyword : Application, Good Corporate Governance